Adaptive immune responses triggered by oxidative stress contribute to hepatic inflammation in NASH. Issue 3 (16th January 2014) - Sutti, Salvatore; Jindal, Aastha; Locatelli, Irene; Vacchiano, Marco; Gigliotti, Luca; Bozzola, Cristina; Albano, Emanuele
<x xml:space="preserve">Abstract</x> Previous studies have shown that human nonalcoholic steatohepatitis (NASH) is often associated with the presence of circulating antibodies against protein adducted by lipid peroxidation products. Here we used the methionine‐choline deficient (MCD) model of NASH to characterize the possible involvement of adaptive immunity in NASH. In mice fed up to 8 weeks with the MCD diet the extension of liver injury and lobular inflammation paralleled the development of immunoglobulin G (IgG) against malonyldialdehyde (MDA) and 4‐hydroxynonenal (4‐HNE)‐derived antigens as well as with the hepatic recruitment of CD4+ and CD8+ T‐lymphocytes responsive to the same antigens. Moreover, in these animals the individual IgG reactivity against MDA‐adducts positively correlated with transaminase release and hepatic tumor necrosis factor alpha (TNF‐α) expression. To substantiate the role of immune responses triggered by oxidative stress in the progression of NASH, mice were immunized with MDA‐adducted bovine serum albumin (MDA‐BSA) before feeding the MCD diet. MDA‐BSA immunization did not affect control mice livers, but further stimulated transaminase release, lobular inflammation, and the hepatic expression of proinflammatory cytokine in MCD‐fed mice. The increased severity of NASH in immunized MCD‐fed mice involved liver recruitment and the T helper (Th)‐1 activation of CD4+ T cells that, in turn, further stimulated macrophage M1 responses. Moreover, hepatic fibrosis was also evident in these animals in relation with an IL‐15‐mediated increase of natural killer T‐cells (NKT) and the up‐regulation in liver production of osteopontin by NKT cells and hepatic macrophages. Conclusion: These results indicate that oxidative stress can contribute to the progression of NASH by stimulating both humoral and cellular immune responses, pointing to the possible role of adaptive immunity in the pathogenesis of the disease. (Hepatology 2014;59:886–897)